2020
DOI: 10.1108/cg-03-2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Moderating role of CEO compensation in lean innovation strategies of Chinese listed family firms

Abstract: Purpose The purpose of this paper is to examine the impact of Chinese listed family firms on lean innovation strategies. Additionally, the authors also examined the moderating role of CEO compensation on the family ownership and lean innovation strategies relationship. Design/methodology/approach Data is obtained from CSMAR database about Chinese family firms listed at Shenzhen Stock Exchange and Shanghai Stock Exchange. Panel data comprising of firm year observations from 2007 to 2016 is analyzed using STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous studies explored the role of traditional governance mechanisms (e.g. compensation (Zulfiqar et al, 2020), employment arrangements (Dobrzykowski and McFadden, 2020)) in aligning principal-agent relationshipour study demonstrates that SLPs can be used for this purpose in a lean implementation context.…”
Section: Empowermentmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies explored the role of traditional governance mechanisms (e.g. compensation (Zulfiqar et al, 2020), employment arrangements (Dobrzykowski and McFadden, 2020)) in aligning principal-agent relationshipour study demonstrates that SLPs can be used for this purpose in a lean implementation context.…”
Section: Empowermentmentioning
confidence: 87%
“…AT is applied to analyze management processes and practices (Eisenhardt, 1988). Previous LT studies have also underscored the importance of taking principal–agent relationships into account by focusing on the role of executive compensation and employment arrangements in successful LT implementation (Zulfiqar et al. , 2020; Dobrzykowski and McFadden, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When family firms design executive compensation system in a highly transparent and principles-based governance framework, their interest in non-financial goals leads to less attention to the relationship between compensation and performance. However, some studies have found that lean innovation of family firms will be negatively regulated by executive compensation, which is the key to reducing agency costs (Zulfiqar et al, 2020) [52].…”
Section: Considerations For Designing Incentive Executive Compensationmentioning
confidence: 99%
“…Keeping in view the current research objectives and earlier discussion, RBV is well suited for this research as different types of family firms are examined for their resource utilization in the form of R&D investment. Although family firms tend to invest lower in R&D as compared to non-family firms, however, getting more output with lesser input is also one of the notable characteristics of family firms (Zulfiqar et al , 2020). Moreover, family entering time is also important as this characteristic may define the varying behaviour of direct-established and indirect-established family firms towards R&D investment.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%